Challenges in the diagnosis and management of wound infection. (19th May 2022) - Malone, Matthew; Schultz, Gregory
Summary: Human epithelia are constantly exposed to microorganisms present in the environment or residing as part of commensal flora. Despite this exposure, infections involving the skin and subcutaneous tissue in healthy individuals are, fortunately, quite rare. Many of the wounds that afflict the human body occur in individuals of ill health and/or where the mechanism of wounding is impeded by host immunological, physiological or regenerative dysfunction. The interplay between microorganisms and host immunity is complex and remains ill defined; however, the interpretation of downstream manifestations of the host response to invading microorganisms is still based largely on the clinical signs and symptoms of an active infectious process. In this review article we will provide a brief overview of the current challenges clinicians face in diagnosing wound infections, how chronic infections caused by biofilms are a major challenge, and how there have been minimal advancements in developing new diagnostics or therapeutics in the identification and management of wound infections. Abstract :